Drug-excipient Interaction Study for Apple Cider Vinegar with 20 Potential Excipients using Modern Analytical Techniques - B Biswal, Dr (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: To evaluate possible interaction between apple cider vinegar (ACV) which is the most frequent used active ingredient of diet pills with 20 different excipients. Materials and Methods: The pure drug ACV and drug-excipient powder mixtures which were stored under the condition of 40Â°C and 75% relative humidity for a period of 21-day and interaction were seen by using modern instrumental technique high-performance liquid chromatography, Fourier transmission infrared and differential scanning calorimetry. To investigate drug-excipient interaction and for selection of suitable excipient for diet pill a comparative study was done and each excipient was selected for formulation development only if it showed compatibility results by at least two instrumental techniques. Results and Discussion: The drug-excipient compatibility study revealed possible interaction between ACV and seven excipients out of 20 different excipients chosen. The excipient where interactions observed with active pharmaceutical ingredient by more than two techniques are magnesium stearate, polyethylene glycol-4000, CARBOPOL, crosspovidone, stearic acid, ethyl cellulose and colloidal silica which could be considered as not suitable for the development of formulation. Conclusion: Study indicates that what are the excipients which can be used for making pill of ACV a useful active ingredient as a diet supplement and antiobesity formulation.